Analysis of flexural fatigue failure of concrete made with 100% Coarse Recycled Concrete Aggregates. (15th January 2016) - Arora, Sumit; Singh, S.P.
Highlights: Flexural fatigue performance of concrete made with 100% RCA has been investigated. Fatigue life distributions for concrete made with 100% RCA established. Higher variation in the fatigue life of concrete made with RCA has been observed. Lower two million cycles endurance limit for concrete made with RCA observed. Abstract: The paper presents results of an investigation carried out to analyze the flexural fatigue performance of concrete beams made with 100% Coarse Recycled Concrete Aggregates (RCA) and its comparison with that of concrete made with 100% Coarse Natural Aggregates (NA). The fatigue performance of concrete beams made with RCA as well as NA has been assessed in terms flexural fatigue life distributions and two-million cycle endurance limit. Experiments were conducted to obtain the flexural fatigue lives of concrete beam specimens made with 100% RCA as well as 100% NA under different stress levels and further compared with literature available on NA. Specimens of size 100 mm × 100 mm × 500 mm were tested under four point flexural fatigue loads applied at a frequency of 10 Hz. It has been shown that the fatigue life distributions of concrete mixes made with 100% RCA and 100% NA can be modeled by the two-parameter Weibull distribution. The values of the shape parameters of the Weibull distribution obtained for concrete made with RCA have been found to be smaller than that of concrete made with NA in present investigation and previous studies on NA, thus indicating higher variability in the distribution of flexural fatigue life of concrete made with RCA viz. a viz. concrete made with NA. The two-million cycles endurance limit for concrete made with 100% RCA has been found to be 50%, which is about 8% and 7% lower than that of concrete made with NA in present and previous studies respectively.